Implementing Problem-Based Learning To Enhance Students' Algorithmic Competence - Namozovich, Khamroev Utkir (Researchparks Publishing, 2024)
This article explores the implementation of problem-based learning (PBL) technology to enhance students' algorithmic competence, a critical skill in the field of computer science and education. Despite the recognized importance of algorithmic competence, there remains a gap in effective teaching methodologies that engage students and foster deep understanding. This study employed a mixed-methods approach, incorporating both qualitative and quantitative data from pedagogical experiments conducted among second-year students at the Navoi State Pedagogical Institute. The findings indicate that PBL significantly improves students' ability to understand and apply algorithms, with the experimental group showing a 9.8% higher mastery rate compared to the control group. The results suggest that integrating PBL into the curriculum can activate cognitive processes, enhance creative thinking, and promote teamwork. These implications highlight the potential of PBL as a transformative educational strategy in developing essential algorithmic skills in students.